1970ネン 1971ネン 1972ネン ニオケル ギンガ ウチュウセンチュウ ノ ヘリウム セイブン - 玉井, 英次; タマイ, エイジ; 境, 孝祐; サカイ, タカスケ; 成田, 信男; ナリタ, ノブオ; 小倉, 紘一; オグラ, コウイチ; 湖上, 晨一; コガミ, シンイチ; TAMAI, Eiji; SAKAI, Takasuke; et al. (国立極地研究所, 1974)
P(論文) Cosmic ray helium flux at the energy around 100 MeV/N was measured by four balloon flights in the summer during the period from 1970 to 1972 at Syowa Station, Antarctica, with the aid of scintillation counter telescopes. The observed helium intensity of 1972 at the energy of 100 MeV/N showed about 100% increase over that of 1970. This value seems to be consistent with the estimated values from the data obtained by Mt. Washington neutron monitor, balloons and satellites in other years. Also the absolute intensity of the present data seems to be 20-30 % higher than the value extrapolated from the data obtained by LEZNIAK and WEBBER in 1965-1968. departmental bulletin paper